Students’ views on database management systems course designed according to problem-based learning - Adem Uzun; Ahmet Onur; Sercan Alabay (International Journal of Evaluation and Research in Education (IJERE), 2020)
The aim of this study was to design a learning environment supported by a problem-based learning method and to obtain students' views on this process. In this context, the Database Management Systems course was taught according to the problem-based learning method. The participants of the study consisted of 25 students from the 2nd-grade students studying in the Department of Computer Education and Instructional Technology in the spring semester of 2015 at Uludag University Faculty of Education. The research design of this study was the case study, which is one of the qualitative research designs. Data were obtained from the students via a semi-structured interview form. Descriptive analysis was applied to the data obtained from the interview. According to the results obtained from the analysis of the data, the students were generally satisfied with the problem-based learning practices. In addition, the students emphasized that it is important to have a sufficient level of necessary knowledge of the implementation of problem-based learning to design the classroom environment.